Spinal Arteriovenous Malformations in A Pediatric Patient: Case Report and Review of Literature (Revista de Medicina Clinica, 2023)
Spinal arteriovenous malformations (sAVM) are rare disorders, comprising approximately 5% to 9% of all vascular malformations of the central nervous system and between 3% to 4% of all spinal cord masses, but which they can present catastrophically as subarachnoid hemorrhage or spinal hemorrhage and also represent an important risk factor for future spinal bleeding. We present the case of a 10-year-old male who started with cervical post-traumatic spinal cord symptoms in whom hemorrhagic MAVE was documented by imaging findings.
Keywords: Arteriovenous malformations; Arterial Embolization; Neck Pain; Cerebral Angiography